2008
DOI: 10.1002/pros.20821
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of novel antiandrogens for neutralizing androgen receptor function in hormone refractory prostate cancer

Abstract: BACKGROUND The standard hormonal therapy with currently available antiandrogens and the leutinizing hormone releasing hormone (LHRH) analogs is not effective in the hormone-refractory stage of prostate cancer due to changes in androgen receptor (AR) signaling axis. In this refractory stage, AR continues to play a significant role in the growth of cancer cells even though the cancer cells are no longer dependent on the level of circulating androgens. METHODS A series of 11β-Δ9-19 nortestosterone compounds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Another option in designing estrogen-SLF conjugates would be to supplement the activity of an antiestrogen by appending an SLF moiety; in fact, such a design has been reported for the androgen receptor (34). We have attempted to create such compounds for the estrogen receptor, but we have had difficulty in synthesizing one that has sufficient ER affinity to be examined in our assays.…”
Section: Discussionmentioning
confidence: 99%
“…Another option in designing estrogen-SLF conjugates would be to supplement the activity of an antiestrogen by appending an SLF moiety; in fact, such a design has been reported for the androgen receptor (34). We have attempted to create such compounds for the estrogen receptor, but we have had difficulty in synthesizing one that has sufficient ER affinity to be examined in our assays.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds have been synthesized with higher affinity for AR than bicalutamide, and that more potently antagonize transcriptional activation via the W741C and T877A mutant ARs (26, 41-44). Another strategy has been to incorporate steric hindrance by linking a potent AR agonist to a ligand of the ubiquitous FK506-binding proteins (FKBPs) (45). A third strategy has utilized a fluorescence based screen to identify compounds that inhibit AR nuclear translocation and the interaction between the N- and C-terminus (46).…”
Section: Novel Antiandrogensmentioning
confidence: 99%
“…The failure of hormonal therapy for prostate cancer has been largely attributed to overexpression of AR in recurrence of the cancer (Chi et al, 2009;Joseph et al, 2009;Norris et al, 2009;Singh et al, 2008;Tran et al, 2009;Zhou et al, 2008). Development of more effective hormonal therapeutic agents targeting overexpressed AR becomes an important research area.…”
Section: Overexpressed Ar and Ar Variants In Crpc As Therapeutic Targetsmentioning
confidence: 99%
“…Many AR antagonists previously developed are mainly ligand competitors for androgens and can not overcome the over-expressed AR in CRPC. Newer approaches have been used to develop agents that can target potential sites in the AR to abrogate the function of the mutated or over-expressed receptor in cancer cells (Chi et al, 2009;Joseph et al, 2009;Norris et al, 2009;Singh et al, 2008;Tran et al, 2009;Zhou et al, 2008;Shen & Balk, 2009). For example, it was reported that a conformation-based assay was used to screen a diverse small molecule library of ≈10,000 compounds in order to select chemicals that can inhibit the AR-gelsolin interaction .…”
Section: Overexpressed Ar and Ar Variants In Crpc As Therapeutic Targetsmentioning
confidence: 99%